Surreptitious TB Infections with Recently Identified DM People: A Cross-Sectional Study - Sireesha, Tanniru; Asha, Syed; Malathi, Jojula (Infectious Disorders - Drug Targets, 2019)
Background: Tuberculosis (TB) among Diabetes Mellitus (DM) population is more expected to fail treatment of TB due to smear-negative TB. Objective: We sought to compare and evaluate different methods to study the frequency of TB infections among DM patients. Methods: Blood, sputum and urine samples were collected from 500 newly identified diabetic patients from different diabetic clinics in Warangal districts. Smear microscopy, Culture and Line Probe Assay by Polymerase Chain Reaction (LPA PCR) were used for identification of tuberculosis. Results: Based on the chest X-Ray of 200 diabetic patients, suspected with pulmonary infections, 113 were males, 85 were females and 2 were children. All 200 patients were tested for tuberculosis infections, 55 were confirmed based on chest X-ray lesions. Off 55 patients, 30 were positive and 25 were negative for AFB microscopy, but were shown positive for chest X-ray. 22 were reported to be culture positive on solid media and identified as Mycobacterium tuberculosis based on morphology and biochemical methods. 36 samples were identified to be positive for LED, FM microscopy and LPA. Off 36 positive samples, 2 were MDR-TB and 34 were MTB based on LPA PCR method. Off 25 smear negative samples, 2 were identified as culture positive and confirmed to be MTB by morphological, biochemical tests. Conclusion: Smear Negative Microscopy plays a vital role in the spread of tuberculosis infection among diabetic patients. Along with the smear microscopy, there is a need to rely on other methods for rapid identification and diagnosis of tuberculosis among the diabetic patients to control the spread of infection in the community and household contacts.
Keywords: Smear positive